Labour Migration, Employer Preferences and Symbolic Boundary Work - Thomas Sæther Jakobsen; Inga Sæther (Nordic Journal of Migration Research, 2023)
A critical stream of scholarship from North America and Europe, on employer preferences for low-wage labour migrants, suggest that the discourse of ‘the migrant work ethic’ works as a euphemism for the exploitability of this mobile, flexible and deferent workforce. In this article, we combine the literature on employer preference and the symbolic boundary approach, to tackle the question of how employer preference for the ‘migrant work ethic’ gains legitimacy. Drawing upon in-depth interviews and ethnographic fieldwork within the fruit and vegetable industry in Norway, we detail how employers narrate the declining employability of the domestic working class, and how migrant workers ascend into the ‘good worker’ category. The recruitment and hiring decisions of the employers form part of a broader moral economy of establishing boundaries to the categories of desirable and undesirable workers. We document how employers establish legitimacy for their recruitment preferences through this boundary work. We argue that this boundary work gains its legitimacy as part of a wider moral economy of ‘employability.’